Being "in a Limbo": Perceptions of Immigration, Identity and Adaptation of Immigrant Students in South Africa and the United States. Issue 3 (3rd May 2016) - Catalano, Theresa; Fox, Jill; Vandeyar, Saloshna
ABSTRACT: Much research is available that details student experiences of immigration and adaptation to receiving countries and schools, but few studies analyze the metaphors used by immigrant students (IS) when talking about the immigration experience, or offer a comparative lens through which to view identity negotiation in two very different contexts. The present paper aims to address these gaps by conducting a comparative linguistic analysis of 20 interviews conducted with IS at universities in South Africa and the United States in order to gain a greater understanding of immigration and the types of identity negotiation processes learners undergo in these very different countries. Findings reveal interesting similarities between metaphorical conceptions of immigration across different cultural contexts and a remarkable resilience in the use of adaptation strategies and identity development that leads to salient pedagogical implications for teachers of higher education who face increasingly international classrooms.